Climate change and COP26: Are digital technologies and information management part of the problem or the solution? An editorial reflection and call to action. (April 2022) - Dwivedi, Yogesh K.; Hughes, Laurie; Kar, Arpan Kumar; Baabdullah, Abdullah M.; Grover, Purva; Abbas, Roba; Andreini, Daniela; Abumoghli, Iyad; Barlette, Yves; Bunker, Deborah; Chandra Kruse, Leona; Constantiou, Ioanna; et al.
Abstract: The UN COP26 2021 conference on climate change offers the chance for world leaders to take action and make urgent and meaningful commitments to reducing emissions and limit global temperatures to 1.5 °C above pre-industrial levels by 2050. Whilst the political aspects and subsequent ramifications of these fundamental and critical decisions cannot be underestimated, there exists a technical perspective where digital and IS technology has a role to play in the monitoring of potential solutions, but also an integral element of climate change solutions. We explore these aspects in this editorial article, offering a comprehensive opinion based insight to a multitude of diverse viewpoints that look at the many challenges through a technology lens. It is widely recognized that technology in all its forms, is an important and integral element of the solution, but industry and wider society also view technology as being part of the problem. Increasingly, researchers are referencing the importance of responsible digitalization to eliminate the significant levels of e-waste. The reality is that technology is an integral component of the global efforts to get to net zero, however, its adoption requires pragmatic tradeoffs as we transition from current behaviors to a more climate friendly society. Highlights: Technology is an integral component of many of the proposed mitigation measures. There exists an urgent need for education on e-waste impact on the environment. Greater focus is needed on responsible digitalization to engender sustained change. Alignment of smart initiatives to SDGs is an underdeveloped research area. Greater awareness is needed on lived in realities of environmental tradeoffs.